The illusion of hell and delayed justice: A dialectical eschatology in the old Javanese swargarohanaparwa - Galang Adhi Pradipta (Life and Death: Journal of Eschatology, 2026)
Background: The transition from mortality to immortality in Old Javanese literature presents a complex interplay of ethics and ontology that challenges linear concepts of karma. This study investigates the eschatological scandal in the Swargarohanaparwa, specifically the Sekar Semawur recension, where the righteous Yudhisthira witnesses Hell while the antagonist Duryodhana enjoys Heaven. While previous scholarship has analyzed this through the lens of moral instruction or ritual symbolism, a gap remains regarding the ontological mechanism of this inversion. This study aims to deconstruct the narrative to understand how Maya (illusion) functions as a necessary dialectic for spiritual liberation (Kalěpasan). Methods: This qualitative study employs a philological and hermeneutic approach. Primary data were collected from the Old Javanese texts of Swargarohanaparwa and Prasthanikaparwa. The analysis integrates the Nirukta (etymological exegesis) method to trace metaphysical meanings and the Dhvani theory (aesthetic suggestion) to uncover implied ontological realities behind the literal descriptions of Hell. Findings: The research argues, based on a philological and hermeneutic reading of the Old Javanese text, that the ‘Hell’ experienced by Yudhisthira can be interpreted not as a retributive location but as a psychological purgatory mediated through the concept of Maya. The textual analysis of Prasthanikaparwa demonstrates that while his brothers died to shed their human defects, Yudhisthira retained his physical body (śarīra mānuṣa), necessitating a final, illusory purification. The visual paradox of Duryodhana in Heaven serves as the antithesis required to force Yudhisthira to transcend the binary of reward and punishment. Conclusion: The study concludes that, within the interpretive framework of Old Javanese textual philosophy, the afterlife is represented not as a static destination but as a dialectical process of self-deconstruction. Novelty/Originality of this article: This research offers a novel interpretation by positioning the "Hell illusion" as an ontological necessity rather than a moral test, contributing a specific Javanese philosophical perspective to the global discourse on the metaphysics of the afterlife.